Le foncier rural dans les pays du Sud Enjeux et clés d'analyse - Colin, Jean-Philippe; Lavigne Delville, Philippe; Léonard, Éric (éditions Quae, 2023)
In the South, access to land and its resources, its control and its uses are crucial issues. At the heart of the challenges of state-building, agricultural development, food security and environmental sustainability, land is also a marker of identity and a recurrent source of conflict. Over the past twenty years, a great deal of research has renewed knowledge on these issues. In a processual and multidisciplinary approach, this book offers an overview of rural land dynamics in the South. Based on a very rich international bibliography, it deals with the main themes related to land issues: from local practices and dynamics (evolution of land rights, land markets, conflicts, etc.) to public policies (agrarian reforms, programmes for the formalisation of land rights), including issues of method and land expertise. Each chapter proposes a critical dialogue between the questions, the categories of analysis and the results of the research. This book is a unique reference tool for students, researchers and development practitioners who wish to deepen their understanding of land tenure dynamics in contemporary rural areas.